NGHIÊN CỨU ĐIỀU KIỆN LAO ĐỘNG VÀ MỘT SỐ CHỈ SỐ SINH LÝ CỦA PHI CÔNG QUÂN SỰ VIỆT NAM LÁI CÁC LOẠI MÁY BAY HIỆN ĐẠI DO LB NGA SẢN XUẤT - Phạm, Xuân Ninh; Trần, Thanh Tuấn; Lê, Tiến Hải; Nguyễn, Minh Hải (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON THE WORKING CONDITIONS AND PHYSIOLOGICAL PARAMETERS OF VIETNAM MILITARY PILOTS WHO FLY RUSSIAN MODERN JET AIRCRAFTThis paper studies the working conditions, physiological parameters of 53 Vietnam military pilots, who flies Russian modern jet aircraft such as MIG-21, SU- 27, SU-30. The results showed that many adverse factors of the labour environment (overload, acceleration, radiation, heat, humidity, noise), the complicated flight tasks and nerve-psychological stress can affect their health during flying period. The microclimatic indexes are higher than the norms and impact directly on the cardiovascular and central nervous system of pilots affecting the functions of organism work capacity and professional health of the pilots.